PENGEMBANGAN MEDIA PEMBELAJARAN MENULIS TEKS FABEL DENGAN MACROMEDIA FLASH BAGI SISWA SMP - Ida Sari Rahmawati; Roekhan Roekhan; Nurchasanah Nurchasanah (Pascasarjana Universitas Negeri Malang, 2016)
This research aims to develop media for learning of fable story wiritng for junior high school students that contain materials, examples, and exercises to achieve the indicators and learning objectives and to describe the feasibility of media for learning gained from expert judgement and field testing. Media for learning developed using macromedia flash program. The development model used was adapted from Borg and Gall development model. Aspect of the assessment in the media for learning is in terms of (1) content, (2) language, and (3) the display. From the results of the expert judgement and field testing, the overall product of learning media has been feasible to be implemented after going through revision stages. Penelitian ini bertujuan mengembangkan media pembelajaran menulis teks fabel bagi siswa SMP yang berisi materi, contoh, dan latihan untuk mencapai indikator dan tujuan pembelajaran serta mendeskripsikan kelayakan media pembelajaran menulis teks fabel bagi siswa SMP yang diperoleh dari uji ahli dan uji lapangan. Media pembelajaran yang dikembangkan menggunakan program macromedia flash. Model pengembangan yang digunakan diadaptasi dari model pengembangan Borg dan Gall. Aspek yang menjadi penilaian dalam pengembangan produk media pembelajaran adalah dari segi (1) isi materi, (2) bahasa, dan (3) tampilan. Dari hasil validasi dan uji lapangan, secara keseluruhan produk media pembelajaran yang dikembangkan telah layak untuk diimplementasikan setelah melalui tahap revisi.